Reconstructing the Islamic Education Paradigm in Indonesia - Al-Razi, Muhammad Fakhruddin; Madjid, Abd.; Khalil, Ahmad Hadziq Madani Ilham (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
Islamic education in Indonesia holds a unique position alongside general education institutions. According to BPS data, the number of Islamic educational institutions and students is about 50% less than that of general education institutions. This research aims to formulate a more inclusive and visionary orientation for Islamic education. Utilizing a literature study method, this research examines several books, journals, hadith, and related verses, supported by explanations from various tafsir books. The study highlights the importance of addressing the worldly goals of humans within Islamic education, emphasizing the need to accommodate the basic needs of human life in the future. It proposes that inclusive and visionary Islamic education should focus on two key aspects: the competence and existence of students. To achieve this, it is essential to eliminate dichotomous barriers or dualism in its organization and policies. The study’s implications call for policies that ensure equal emphasis on both general and religious subjects in Islamic educational institutions, moving away from a two-path policy.